2011
DOI: 10.1002/j.2334-5837.2011.tb01287.x
|View full text |Cite
|
Sign up to set email alerts
|

11.2.2 Reducing the Gap Between Formal and Informal Worlds in Automotive Safety‐Critical Systems

Abstract: Abstract. The upcoming ISO26262 standard, which deals with the functional safety of road vehicles, will induce car manufacturers to adapt the way in which vehicle systems are usually developed. To achieve this, more rigorous development processes along with new tools and techniques will most certainly be necessary. This paper presents an overview of current initiatives at Renault dealing with the improvement of development processes for mechatronic systems to comply with ISO 26262. It focuses on introducing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This generated a strong divergence in how to express patterns, thus reducing the capability to reuse them as is. However, some research has shown how the gap can be reduced by introducing more formalization inside the SE design process via the definition of an ontology to formalize concepts [80]. In accordance with this, the current request for proposal for the future version 2 of SysML (mentioned previously in section V.A.)…”
Section: Limits Of Patterns In An Mbse Frameworkmentioning
confidence: 84%
“…This generated a strong divergence in how to express patterns, thus reducing the capability to reuse them as is. However, some research has shown how the gap can be reduced by introducing more formalization inside the SE design process via the definition of an ontology to formalize concepts [80]. In accordance with this, the current request for proposal for the future version 2 of SysML (mentioned previously in section V.A.)…”
Section: Limits Of Patterns In An Mbse Frameworkmentioning
confidence: 84%
“…The conceptual model in Chalé et al (14) deals with links between systems engineering and ISO 26262 (3) but it is too generic to satisfy requirements 3 and 5. There is a unique view and concepts are not classified according to the processes.…”
Section: Tablementioning
confidence: 99%
“…As Chalé et al (14) or Deniaud et al (15), the conceptual model we propose in this section is based on the analysis of key standards: IEEE 1220 (16), ISO 15288 (10) for Systems Engineering concepts and ISO 26262 (3) for safety concepts. In order to fulfill the above requirements, the model is divided into three views corresponding to the three main processes of system design (Requirements Analysis, Functional Architecture Design and Physical Architecture Design).…”
Section: Tablementioning
confidence: 99%
“…The application of ontology engineering in systems engineering seems to be a very promising trend [12], [4]. We call it system verification based on Knowledge Management, and it deals with assisting System Engineers to get a complete and consistent set of requirements (e.g.…”
Section: Introductionmentioning
confidence: 99%